What happens during the creation of private property? Subdividing group ranches in Kenya's Maasailand - Mwangi, Esther (International Food Policy Research Institute, 2009)
This case study discusses the internal processes and decisions that characterized the transition from collectively held group ranches to individualized property systems among the Maasai pastoralists of the Kajiado district in Kenya. It examines who the main actors were during subdivision, their interactions (including their degree of latitude in crafting and changing rules), as well as the outcomes of these interactions.